Patterns of industrial structural change: Biobio region, Chile. 1974-1989. - Urrea, Jorge. (University of Ottawa (Canada), 1992)
Chile's recent experience with the liberalization of foreign trade provides a singular case study because of: the high level and many types of tariff protection before the reforms; the extraordinary effect of rapid trade policy liberalization; and the current structure that the country's economy has assumed. The protection of Chile's manufacturing began after the Great Depression and gradually increased after the second World War. However, from 1973 a profound economic reform radically changed the traditional protectionism shielding the Chilean economy. This paper analyzes the adjustment of industrial firms to both trade liberalization and policy reforms for stabilization, during the military regime. The study is conducted using two hypotheses that link manufacturing firms to their location in the region and to the final destination of their production. The main conclusions of the study suggest the advantages and disadvantages that the present industrial structure of the region might face as a consequence of its specialization. They summarize changes of both internal and external conditions that have been favourable to regional industrial growth. Internally there has been industrial specialization according to the comparative advantage of the Biobio region in natural resources. External influences have driven a shift to capital intensive sectors, which have grown rapidly relative to other manufacturing sectors, and have replaced labour-intensive sectors as the dominant component of the regional industrial base. The overall result is that the structure of manufacturing in the Biobio region has changed in a process of restructuring different from that anticipated and predicted by free trade theorists.
Keywords: Business Administration, General.